Movimentação dentária induzida com dois diferentes tipos de ancoragem em ratos: achados dimensionais, radiográficos e histológicos - Araújo, Vilana Maria Adriano (2022)
Induced tooth movement (ITM) promotes microscopic and macroscopic changes, which culminate in cellular responses and can be induced by the application of force in an animal model. The objective was to quantify the ITM with two different types of anchorage in rats, through dimensional, radiographic and histological findings. For this, 66 Wistar rats were used, which were divided into two groups: one used anchorage in the upper incisors (IG) and the other in mini-implants (MG). The animals were submitted to the installation of a CrNi spring (50 cN), which was fixed around the maxillary left first molar and maxillary incisors, or to the mini-implant. The contralateral hemiarch was used as the control group (CG). The animals were euthanized on days 7, 14 and 21. Macroscopic measurements were performed, which were compared to those obtained on the day of device installation (D0). In the histological analysis, interproximal distances were measured and pulp and periodontal scores were assigned. In the histochemical analysis, total collagen, type I and type III were quantified. Macroscopic measurements demonstrated a tooth displacement in the dental and skeletal anchorage, with a palatinization of the incisors in the IG. Although there was a loss of anchorage on the 21st day in the MG (p<0.00001), in relation to the D0, this was maintained up to 14 days. In the histological measurement of the interproximal distance between the 1st and 2nd molars, a significant increase (p<0.0001) was observed in all times of the groups, in relation to the CG. In the radiographic analysis, there was a significant difference in the MG at 14 and 21 days, in relation to the CG (p<0.0001). In the IG, this increase occurred in 21 days (p<0.0001). In the histological analysis, pulp alterations were observed in the period of 21 days in IG and MG. The periodontal parameters were significant in all periods, in relation to the CG. In the histochemical analysis, a significant increase in total collagen was observed after 21 days in IG (p=0407) and MG (p=0.0017), in relation to CG. In the quantification of collagen type I, there was an increase in 7 days in MG (p=0.0171), while, in collagen type III, there was an increase in 14 and 21 days in MG (p=0.0132; 0.0006), in relation to the GC. The findings showed that ITM with skeletal anchorage was more effective. Furthermore, it was possible to find data that suggest greater collagen remodeling. Dental anchorage, despite having presented important results, has a considerable disadvantage, which is the inclination of the incisors.